Properties of Clear Coated Spruce (Picea orientalis) and Beech (Fagus orientalis) Woods for Evaluating Outdoor Utilizations - Sahin, Candan Kus; Merdan, Rahim (European Journal of Applied Sciences, 2025)
It has become an important issue for protecting wood that is not harmful to users, while wooden design elements provide many opportunities and amenity to visitors. Some new types of wood-protecting agents have gained importance due to their low-toxic chemical formulations. The study presents the experimental study on outdoor exposure impact on clear coated of two different of Spruce and Beech wood species. It was found that increasing coating number is usually having positive effects, lowering the water absorption of both spruce and beech woods. The lowest water absorption value of 1.7% found at fifth-time coated beech wood, which shows approximately 97.2% lower than the control sample. However, increasing coating time (durations) was found to have further lowering effects on water absorption for beech wood species. It was found that the three-month duration of weathering was not affected by the surface scratch resistance (hardness) of control spruce and beech woods, while it is usually increasing effects on waterborne varnish-treated samples regardless of treatment conditions. This is clearly indicating physicochemical modification and creating tension on wood surfaces in outdoor conditions. However, weathering significantly affects the surface color and gloss properties of selected wood samples. The increasing coating layer was found to be not affected by improving lightness values for spruce wood. The similar trend was also observed with treatment time up to 3.0 min, and beyond this level, the wood surfaces were found to be lighter (ΔL: + values). Moreover, varnish treatment variables (coating layer and time) were also not any improvement effects found for beech wood. The lowest ΔL value of-9.78 (in metric) was found for sample Be, followed by B4 (ΔL:-9.38) and B5 (ΔL:-9.0), samples, respectively. It is important that the surface total color difference (ΔE) of wood substrates appeared to be well correlated with coating number and time of duration for both spruce and beech woods. It was realized that increasing the coating number is not effective for improving gloss properties for spruce wood, while some variations in glossiness for beech wood could be realized by changing the treatment parameters.